Arti Penting Ruang Hijau Kota bagi Masyarakat dan Pemerintah Kota (Ruang Hijau Kota di Lyon, Prancis) - Fitriandana, Bima; Wittner, Laurette; Syahbana, Joesron Alie (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
The appearance of different urban green space phenomena occuring both in developing and developed countries appeals to be found out in research. Urban green space hasn’t been an essential element in developing countries, such as in Indonesia and its big city. In another part, precisely in Lyon, urban green space is considered as an intergral and important part of city development, particularly in last 24 years (begun in 1990’s). Moreover, their people actively participate in some urban green space projects and go frequently in urban green spaces or urban parks. By indentifying those two phenomena, it’s vividly seen a problem both in societal and municipal level. Based on those facts, this research tried to find out a research question which is about the importance of urban green space for society and minicipality. This research that has been conducted in Tête d’Or park, gerland park, Sergent Blandan park, the river bank of Saône and Rhône as well as Mazagran park, used qualitative methode with some interviews reserved to some key actors, including society. The result shows that society regards urban green space as a source of benefit for social, education and health. Whereas, municipality considers it as an integral element of city providing environmental and economic benefit for city.